2015
DOI: 10.17140/aftnsoj-1-e001
|View full text |Cite
|
Sign up to set email alerts
|

Maca: Botanical Medicine from the Andes

Abstract: CitationRosales-Hartshorn M. Maca: Botanical medicine from the andes. Adv Food Technol Nutr Sci Open J. 2015; 1(2): e1-e6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The edible part of maca, the hypocotyl, has been widely used to treat osteoporosis [ 65 ]. Ethanol extract of maca has anti-osteoporotic activity and indicated maca alkaloids, steroids, glucosinolates, isothiocyanates, and macamides are probably responsible for its biological functions [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The edible part of maca, the hypocotyl, has been widely used to treat osteoporosis [ 65 ]. Ethanol extract of maca has anti-osteoporotic activity and indicated maca alkaloids, steroids, glucosinolates, isothiocyanates, and macamides are probably responsible for its biological functions [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro/in vivo animal experimental studies have shown that secondary metabolites extracted from maca have bioactivities that help treat osteoporosis and enhance prostate function and sexual function [ 19 21 ]. However, most in vitro and in vivo experiments have not specified the molecular target of these secondary metabolites and the mechanisms of the functions of the compounds obtained from maca are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, El-Sheikh et al [55] reported that maca-treated rabbit does have a numerically higher concentration of E2 hormone and a lower concentration of P4 hormone than those in the control group. This and the enhancement of serum LH levels may be the mechanisms that improve fertility [87]. The positive effects of maca may be due to saponins, which play an important role in sex hormone secretion and the treatment of sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%